Revolutionizing Education for Women Empowerment during Pandemic and Post-Pandemic Times (International Journal of Multidisciplinary Perspectives in Higher Education, 2023)
Women are underrepresented and denied equal opportunities in the scientific community as a result of a rigid research culture and a lack of genuine academic support. Higher Education should go beyond the superficial treatment of women's empowerment. This article reflects on the heightened gender-based inequality during pandemic and calls for the academic community to take social action and contribute to women empowerment. It also advocates re-creating and revolutionizing the educational system to promote women's rights and welfare in pedagogical instruction, as well as involving more men as one of the potential solutions to strengthen women's empowerment. Higher Education should create and encourage more research opportunities and amplify policy spaces for women amid the fight against COVID-19. Academia should therefore adopt a feminist lens as an integral part of its structure to enact social change, because women empowerment is beyond mediocrity.